Giải các phương trình : (√2 -1)^x2-5x+4=(3+2√2)^x-1

Question

Giải các phương trình :
(√2 -1)^x2-5x+4=(3+2√2)^x-1

in progress 0
Lyla 4 tuần 2021-08-25T07:10:18+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-25T07:11:54+00:00

    Đáp án: $ x=1\quad or\quad x=2$

    Giải thích các bước giải:

          $(\sqrt[]{2}-1)^{x^2-5x+4}=(3+2\sqrt[]{2})^{x-1}$ 

    $\rightarrow (\sqrt[]{2}-1)^{x^2-5x+4}=(2+2\sqrt[]{2}+1)^{x-1}$ 

    $\rightarrow (\sqrt[]{2}-1)^{x^2-5x+4}=((\sqrt[]{2}+1)^2)^{x-1}$ 

    $\rightarrow (\sqrt[]{2}-1)^{x^2-5x+4}=(\sqrt[]{2}+1)^{2x-2}$ 

    $\rightarrow (\sqrt[]{2}-1)^{x^2-5x+4}.(\sqrt[]{2}-1)^{2x-2}=(\sqrt[]{2}+1)^{2x-2}.(\sqrt[]{2}-1)^{2x-2}$ 

    $\rightarrow (\sqrt[]{2}-1)^{x^2-5x+4+2x-2}=((\sqrt[]{2}+1)(\sqrt[]{2}-1))^{2x-2}$ 

    $\rightarrow (\sqrt[]{2}-1)^{x^2-3x+2}=1^{2x-2}$ 

    $\rightarrow (\sqrt[]{2}-1)^{x^2-3x+2}=1$ 

    $\rightarrow x^2-3x+2=0$ 

    $\rightarrow (x-1)(x-2)=0$ 

    $\rightarrow x=1\quad or\quad x=2$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )